2012
DOI: 10.1038/emboj.2012.257
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for Arl3-specific release of myristoylated ciliary cargo from UNC119

Abstract: Access to the ciliary membrane for trans-membrane or membrane-associated proteins is a regulated process. Previously, we have shown that the closely homologous small G proteins Arl2 and Arl3 allosterically regulate prenylated cargo release from PDEd. UNC119/HRG4 is responsible for ciliary delivery of myristoylated cargo. Here, we show that although Arl3 and Arl2 bind UNC119 with similar affinities, only Arl3 allosterically displaces cargo by accelerating its release by three orders of magnitude. Crystal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
125
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 44 publications
4
125
0
Order By: Relevance
“…As predicted from sequence signatures, 22 structural studies of Arf-like and Arf-related GTPases, including Golgi Arl1, 74,75 cilium Arl3 76,77,78 and Arl6 79 and endoplasmic reticulum Sar1 80,81 have now shown that autoinhibition by the N-terminal extension and the interswitch takes place in these GTPases and is released by the displacement of the N-terminus and the toggle of the interswitch. Thus, the allosteric mechanism that uses the displacement of the N-terminal extension as a priming event to autoinhibition release and the remodeling of the interswitch as the means whereby information is propagated to the nucleotide-binding site is probably general to the entire Arf-like family.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…As predicted from sequence signatures, 22 structural studies of Arf-like and Arf-related GTPases, including Golgi Arl1, 74,75 cilium Arl3 76,77,78 and Arl6 79 and endoplasmic reticulum Sar1 80,81 have now shown that autoinhibition by the N-terminal extension and the interswitch takes place in these GTPases and is released by the displacement of the N-terminus and the toggle of the interswitch. Thus, the allosteric mechanism that uses the displacement of the N-terminal extension as a priming event to autoinhibition release and the remodeling of the interswitch as the means whereby information is propagated to the nucleotide-binding site is probably general to the entire Arf-like family.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 99%
“…The N-termini of Arfrelated GTPases vary in length, sequence and post-translational modifications, and there is therefore ample reasons to believe that they are displaced in different ways to release autoinhibition. For instance, the N-terminus of Arl3-GTP interacts with another protein, 77,78,82 and it is conceivable that there exists Arf-like GTPases in which autoinhibition release involves interactions of the Nterminus with both a protein and a membrane. Understanding this process will be a major theme for future investigations of the molecular mechanisms that regulate the activity of Arf-like GTPases.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 99%
“…INPP5E showed an approximately 100 fold higher binding affinity to PDE6d with a dissociation constant in the nanomolar range as compared to submicromolar affinities for Ras and Rheb. 46 Stimulated by the findings that only Arl3 can release high affinity ciliary cargo from Unc119 12,15 and from PDE6d, 38 we could confirm that under identical concentrations only Arl3 is able to release a C-terminal prenylated INPP5E peptide from its complex with PDE6d, while Arl2 did not. 46 Kinetic studies showed that the stimulated release of farnesylated INPP5E peptide by Arl3 GTP is 600fold faster than by Arl2 GTP.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 57%
“…The binding of type 1 and type 2 effectors is nevertheless mutually exclusive. 8,9,[13][14][15] Functional differences between Arl2 and Arl3…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 99%
See 1 more Smart Citation